Technical communication : principles and practice - Raman, Meenakshi; Sharma, Sangeeta (Professor in English) (Oxford University Press, 2015)
Technical Communication: Principles and Practice, now in its third edition, discusses the core concepts of technical communication, explaining techniques with the help of numerous examples and practice exercises. With its in-depth coverage and practical orientation, this book is useful not only for students, but also as reference material for corporate training programs.